Condylar pathway changes following different treatment modalities - (:unkn) unknown (OXFORD UNIV PRESS, 2003)
The purpose of this investigation was to evaluate the effect of extraction and non-extraction approaches on the condylar pathways in subjects treated with fixed orthodontic appliances. The study was carried out on 70 patients (47 female, 23 male) who had undergone orthodontic treatment with fixed appliances. The mean age for the total group was 16.3 years (16.5 years for the females and 16 years for the males). Forty-seven patients were treated non-extraction and 23 with extractions. None of the patients had any temporomandibular joint (TMJ) problems before orthodontic treatment and all were treated with standard edgewise mechanics. The condylar pathway recordings were taken before and after treatment with an axiograph. The maximum opening capacity was measured and the right and left condylar pathways of each patient were recorded in protrusion and during opening movements. During treatment the left opening angle (LOA) only decreased significantly in the upper premolar extraction group. The left opening distance (LOD) decreased in all groups during treatment but was only statistically significant in the non-extraction and upper and lower extraction groups. In the small overjet group (OJ less than or equal to 4 mm), the LOA, right opening distance (ROD) and LOD decreased significantly while there was no significant change in axiographic parameters in the large overjet group (OJ > 4 mm). In the latter group, overjet and overbite decreased while mouth opening (3 mm P < 0.05) significantly increased. These results indicate that there is no difference between the effect of different treatment protocols on the condylar pathways.
Keywords: TEMPOROMANDIBULAR-JOINT DYSFUNCTION; JAW MOVEMENT OBSERVATIONS; ORTHODONTIC TREATMENT; MANDIBULAR DYSFUNCTION; PREMOLAR EXTRACTIONS; COMPUTERIZED AXIOGRAPHY; DISORDERS TMD; POSITION; SYMPTOMS; OCCLUSION